PENYULUHAN DAN PELATIHAN PENGOLAHAN SABUT KELAPA - M. Amin, Tuasikal (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Coconut (Cocos nucifera) is the sole member of the clan of the tribe palm Cocos-arenan or Arecaceae. This plant is used almost all parts by humans that is considered as a versatile plant, especially for coastal people. With such conditions, it is unfortunate people at Desa Kebonharjo, Kecamatan Samigaluh, Special Region of Yogyakarta yet have insight into the coco fiber processing. Often, coconut only considered as waste that can not be used. Therefore, the authors initiated counseling and training held coco fiber processing. With hope, which was originally unused waste can be processed into goods more useful. Furthermore, the processed results can be used as a commodity trading high profit.